FREQUENCY OF HELMINTHS IN WILD WHITE-LIPPED PECCARIES (TAYASSU PECARI LINK, 1795) FROM PROTECTED AREAS IN MADRE DE DIOS DEPARTMENT, PERU - Carlos, Nancy (2008)
Parasites of wild populations play an important role in the control of ecological communities andecosystems. Information about host ecology are essential to the proper analysis of the epidemiologicalprofile to be considered during process of maintenance of hosts. Moreover, helminths infecting the whitelipped peccary (Tayassu pecari) from the Peruvian Amazon are unknown, so far. The aim of the present study was to identify and determine the frequency of helminths parasitizing wild peccaries from Madre de Dios Department, Peru. Thirty-three fecal samples preserved in 10% formaldehyde were analyzed by means of the direct method and Ritchie's method (formaldehyde-ether). The total amount of positive samples were of 81.81%. Of these, 81.81% and 12.12% showed the presence of nematode and trematode eggs, respectively. Nematodes were represented by Ascaris sp. (51.51%), ancylostomatids (33.33%), and spirurids (6.06%), as well as the trematode Paragonimus sp. (12.12%). The present survey deals with the first report of the presence and frequency of worms infecting wild specimens of the white-lipped peccary in Peru; T. pecari is here established as a new host record for Paragonimus sp.